Safety and immunogenicity of trivalent inactivated influenza vaccine in adults 60 years of age and older: a phase II, a randomized, comparative trial in Kazakhstan. Issue 8 (2nd August 2020) - Sarsenbayeva, Gulbanu; Issagulov, Timur; Kassenov, Markhabat; Abitay, Ruslan; Orynbayev, Mukhit; Stukova, Marina; Pisareva, Maria; Davlyatshin, Timur; Lespek, Kutumbetov; Khairullin, Berik
ABSTRACT: Background: The study was aimed at comparative evaluation of seasonal influenza vaccine RIBSP versus commercial vaccine VAXIGRIP® for immunogenicity and safety in the course of clinical trial phase II on healthy subjects up to 60 years. Methods: The trial involved 150 subjects in randomized 2:1 groups that received either RIBSP vaccine or comparator vaccine VAXIGRIP®. One dose (0.5 ml) of either vaccine contained 15 µg of hemagglutinin of each influenza virus strain recommended by WHO for the Northern hemisphere in 2016–2017 flu season. The observation period lasted 21 days. The trial was registered at ClinicalTrials.gov identifier NCT 03016143. Results: Assessment of immunogenic activity of the vaccine under study showed that in 21 days the portion of participants with 4-fold seroconversions was 80.0% to А/H1N1; 65.0% to А/H3N2 and 64.0% to B virus. Antibody titer increase factor in the group of subjects that received RIBSP vaccine was 13.4 for А/H1N1; 5.2 for А/H3N2 and 5.2 for B virus. The subjects that received RIBSP vaccine demonstrated 88% seroprotection rate against А/H1N1; 75% against А/H3N2 and 61% against B virus. In the course of evaluating the vaccine safety, no serious adverse events were recorded. All changes of laboratory data were slight and single in most cases. All recorded local reactions have been light in character and these have been predicted reactions observed at vaccination against influenza. Conclusion: Comparison vaccines RIBSP and VAXIGRIP®, showed similar immunogenic activity. The RIBSP vaccine is safe and immunogenic for the elderly and conforms to international criteria in CPMP/BWP/214/96.